Korelasi Propertis Biodiesel Terhadap Emisi Gas Buang dan Performa Mesin Diesel - Syarifudin Syarifudin; Heru Nur Cahyo; Agus Suprihadi (P3M Politeknik Negeri Cilacap, 2020)
Biodiesel is a priority program to reduce dependence on diesel fuel. B20 biodiesel is proven to be used as fuel without modifying diesel engine specifications. The development of biodiesel with a higher percentage of palm oil need to be developed continuously, therefore dependence on diesel fuel is lower. However, the high viscosity of biodiesel becomes an obstacle, so alcohol is added to reduce problems in the fuel injection process. This research aims to observe the biodiesel properties of a solar-palm cooking oil-methanol/ethanol/butane mixture which is correlated with the potential exhaust emissions and performance produced by a diesel engine. Palm cooking oil used is 30%, 40%, 50%, 60%, 70%, 80%, and 85%, while methanol/ ethanol/ butane alcohol used is 15%. Based on the results of physical and chemical tests, the higher the content of palm cooking oil means the worse the biodiesel properties will be. Biodiesel blended of palm-methanol solar-cooking oil has the potential of the same exhaust emissions and engine performance as diesel fuel.